Experimental and fractional analysis of half-value thicknesses of polyethylene absorber - Çalık, A. E.; Sirin, H.; Şen, M. (Revista Mexicana de Física, 2020)
In this study, half-value thicknesses and mass attenuation coefficients of polyethylene absorber have been measured experimentally using the beta sources 99Tc, 147Pm, 137Cs, 204Tl, 210Pb and 36Cl. There is an inconsistency between experimental and calculated values of half value thicknesses obtained with the help of standard attenuation equation. In order to overcome this discrepancy, the fractional attenuation equation which was redefined and resolved using Caputo fractional derivative has been used. The theoretical results obtained according to this new equation are in agreement with experimental results around 0.3 value of the order of fractional derivative.